Demographic Profile of The English Speaking Communities in the Administrative Region of Montérégie & MRC Les Jardins de Napierville - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC les Jardins de Napierville (16042) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.